Application of the rotational thromboelastography/thromboelastometry for assessment of massive obstetric blood loss in a high risk group - D. R. Eremeeva; M. S. Zainulina (IRBIS LLC, 2020)
Here, we discuss blood management upon a risk of massive obstetric hemorrhage by describing a clinical case of female patient with obstetric complications of pregnancy such as severe preeclampsia and chronic placental insufficiency with fetal malnutrition examined by using thromboelastometry to assess a risk of developing massive obstetric hemorrhage. A rotational thromboelas-tography/thromboelastometry technology as well as available publications related to using it in obstetrics are outlined.